TERAPI TERKINI MULTIPLE MYELOMA - Suega, Ketut; Sripurnama Sjah, Yunny (journal of internal medicine, 2012)
Management strategies for Multiple Myeloma (MM) have continued to evolve as the result of innovative treatment modalities and efÞ cacy data used in establishing new standard of care. In 2004, multiple myeloma was diagnosed in more than 15.000 people in the United States and will account for approximately 20% of deaths due to hematologic malignancies. Most commonly diagnosed in the growing elderly population. Until recently, few effective treatment existed. The use of alkylating agents and corticosteroid had remained the treatment of choice for almost four decades. On a cellular level, the disease is characterized by complex interactions between tumor cells and the surrounding bone marrow microenvironment. Understanding of the relationship between malignant plasma cells and the microenvironment has sparked ongoing efforts to develop targeted therapeutic agents for treatment of this disease. Recent advances in its treatment including using of the immunomodulatory drugs such as thalidomide and lenalidomide as well as the proteasome inhibitor bortezomib. Each of these agents is undergoing extensive clinical evaluation in combination with other therapies to produce unprecedented response rates in newly diagnosed and relapsed MM. They have each improved the response to therapy, but they are expensive. In recent years, evidence supporting a survival beneÞ t for three new drugs have resulted in their inclusion, in combination with older drugs, in the management of younger and older patients. Each of these new drugs has multiple mechanisms of action, targeting both intracellular signaling pathways and tumor microenvironment. This review focus on the newer agents such as thalidomide, bortezomib, and lenalidomide in treatment of patient with newly diagnosed MM and relapsed MM, treatment-related side effect, and future using of these agent including new combination therapy
Keywords: multiple myeloma, thalidomide, bortezomib, lenalidomide, combination therapy